Travel Abroad for Face Gaining or Face Saving? A Comparison Between Chinese Gen Y Male and Female Tourists in a Context of Chinese Culture. Issue 1 (20th January 2022) - Long, Fei; Aziz, Norzalita Abd
Abstract: "Face" is considered one of the most important cultural values in China, but there is insufficient research discussing the effect of "face" on outbound travel behaviors among Chinese Gen Y tourists. Most of the previous studies have oversimplified "face" as a uni-dimensional concept in tourism. However, the relevant literature suggests that an individual may behave differently when s/he is concerned about gaining "face" or losing "face." Furthermore, gender plays an important role in influencing travel behaviors in China. Therefore, this research establishes a conceptual framework based on "face" and TPB to explore whether Chinese Gen Y travel abroad for face gaining or face saving, and compares the influence of "face" across gender. By analyzing data from 155 males and 195 females, it is found that there are significant differences in relation to the effect of "face" on outbound travel intention across gender. Chinese Gen Y females travel abroad mainly to gain "face, " and their male counterparts travel abroad mainly to avoid losing "face." The gender-based differences reaffirms that Chinese society has different evaluation criteria for men and women, and their travel behaviors consequently are shaped by gender norms. This study facilitates our understanding of Chinese Gen Y tourists and China's outbound tourism market from both Chinese and Western epistemologies. Then, practical implications and limitations are discussed accordingly.